Psychosocial aspect determines quality of life in postmenopausal women - Wratsangka, Raditya (Universa Medicina, 2010)
The postmenopausal period plays an important role in womenâs life and gives rise to many physical and mental problems. A cross-sectional was conducted to determine the quality of life and its determinants, namely pyschosocial and lifestyle factors in postmenopausal women. One hundred and seventy-six postmenopausal women meeting the inclusion criteria were recruited. TheÂ Â Â Â Â Â Â Â Â Â Â  menopause rating scale (MRS) questionnaire was used for the assessment of quality of life. One hundred and thirty-one (74.4%) subjects had complaints related to menopausal symptoms in 3 degrees of severity: mild (38.6%), moderate (30.7%) and severe (5.1%). Urogenital symptoms were the most frequentÂ Â Â Â Â Â  complaints reported by the subjects (71.6%). The correlation between quality of life ofÂ Â  postmenopausal women and several psychosocial and lifestyle factors, namely marital status, education, occupation, knowledge and attitude towards menopause, exercise, smoking and consumption of caffeine and alcohol was statistically not significant (p>0.05). By multiple logistic regression analysis, some of the determinants, such as the subjectsâ attitude towards menopause (PR = 2.863; 95% CI: 0.578 â 14.185) and support from the husband and/or family (PR = 2.124; 95% CI: 0.979 â 4.610) did not reach statistical significance, but were still the most influencing factors on their quality of life. Quality of life is worst in postmenopausal women and therefore counseling and support from husband and/or family are needed by the postmenopausal women in order to improve their quality of life.